Population-specific, biogeocenotic and Biosphere Biological Organisation - Prykhodko, A. B.; Popovich, A. P.; Yemets, T. I.; Maleeva, A. Y.; Приходько, Олександр Борисович; Попович, Аліса Петрівна; Ємець, Тетяна Іванівна; Малєєва, Ганна Юріївна (Zaporizhzhia state medical university, 2017)
Medical Parasitology is a fundamental discipline within the medical sciences. Study of the structure, organization and life-cycles of different parasites gives the doctors strong knowledge about parasitizm for searching the most effective methods of treatment. The present Text Book for the first year training students of the Medical faculty has been written in accordance with the Academic Curriculum on Medical Biology accepted by all Medical University of Ukraine. Efforts have been made to provide latest material facts. Improved illustration wherever necessary are provided, for a better understanding of the subject by the students. Detailed discussions, a range of test questions continue to be the main attractions of the book.